Solid dan liquid kompos untuk mendukung pangan lestari di Gampong Bueng Pageu Kecamatan Blang Bintang Aceh Besar [Solid and liquid compost to support sustainable food in Bueng Pageu Village, Blang Bintang Sub-District, Aceh Besar] - Muyassir, Muyassir; Jufri, Yadi; Helmi, Helmi; Manfarizah, Manfarizah; Fazlina, Yulia Dewi; Khairani, Cut (Universitas Syiah Kuala, 2024)
The purpose of the service is to support the realization of sustainable food in Bueng Pageu Village, Blang Bintang Sub-District, Aceh Besar District. The activity is through increasing the capacity of farmers and PPLs with the technology of making solid and liquid compost easily and simply. The method used is a field school that involves the participation of farmers and PPLs directly who were previously given training on the technique of making solid and liquid compost and how to use it. The results of the activity showed that there has been an increase in the knowledge capacity of farmers in the manufacture and application of solid and liquid compost fertilizers reaching 52.87%. The decomposition process in producing solid compost takes 4 weeks, the results obtained are around 1200 kg with a potential economic value of Rp. 3,120,000 and 50 L of liquid compost with an economic value of Rp. 1,750,000. Making compost from agricultural waste and household waste can increase the community's revenue while overcoming health problems and environmental aesthetic value.